2021
DOI: 10.1186/s13287-021-02149-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the long noncoding RNA H19 in osteogenic differentiation and bone regeneration

Abstract: Osteogenic differentiation and bone regeneration are complex processes involving multiple genes and multiple steps. In this review, we summarize the effects of the long noncoding RNA (lncRNA) H19 on osteogenic differentiation.Osteogenic differentiation includes matrix secretion and calcium mineralization as hallmarks of osteoblast differentiation and the absorption of calcium and phosphorus as hallmarks of osteoclast differentiation. Mesenchymal stem cells (MSCs) form osteoprogenitor cells, pre-osteoblasts, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 70 publications
2
19
0
Order By: Relevance
“…Further studies are warranted to validate these observations and inferences. Previous studies also reported that H19 heightened osteogenic differentiation of BMSCs [14,25,26]. Consistently, H19 expression was upregulated during BMSC osteogenic differentiation in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Further studies are warranted to validate these observations and inferences. Previous studies also reported that H19 heightened osteogenic differentiation of BMSCs [14,25,26]. Consistently, H19 expression was upregulated during BMSC osteogenic differentiation in this study.…”
Section: Discussionsupporting
confidence: 91%
“…LncRNA H19 is among the most abundant and conserved non-coding transcripts during mammalian development, which is widely involved in the process of osteogenic differentiation of stem cells and contributes to maintaining the osteogenic process of cells [ 32 ]. Several studies have demonstrated that H19 is highly expressed during the induction of osteoblastic differentiation of MSCs, and it promotes osteoblastic differentiation by regulating the Wnt/β-catenin activation through miR-141/miR-22 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult bone mass is maintained in homeostasis. To accomplish this, new bone formation replaces old bone tissue so that bone mass maintains a dynamic balance (Zhou et al 2021 ). Osteoblasts, osteoclasts, and osteocytes are the main cells involved in this bone remodeling process.…”
Section: Discussionmentioning
confidence: 99%